A biogeographical profile of the sand cockroach Arenivaga floridensis and its bearing on origin hypotheses for Florida scrub biota. Issue 11 (15th May 2018) - Lamb, Trip; Justice, Teresa C.; Brewer, Michael S.; Moler, Paul E.; Hopkins, Heidi; Bond, Jason E.
Abstract: Florida scrub is a xeric ecosystem associated with the peninsula's sand ridges, whose intermittent Pliocene–Pleistocene isolation is considered key to scrub endemism. One scrub origin hypothesis posits endemics were sourced by the Pliocene dispersal of arid‐adapted taxa from southwestern North America; a second invokes Pleistocene migration within eastern North America. Only one study to date has explicitly tested these competing hypotheses, supporting an eastern origin for certain scrub angiosperms. For further perspective, we conducted a genetic analysis of an endemic arthropod, the Florida sand cockroach ( Arenivaga floridensis ), with two aims: (1) to reconstruct the peninsular colonization and residence history of A. floridensis and (2) determine whether its biogeographic profile favors either origin hypothesis. We sequenced the cox2 mitochondrial gene for 237 specimens (65 populations) as well as additional loci ( cox1, nuclear H3 ) for a subset of Florida roaches and congeners. Using Network and Bayesian inference methods, we identified three major lineages whose genetic differentiation and phylogeographical structure correspond with late Pliocene peninsula insularization, indicating Arenivaga was present and broadly distributed in Florida at that time. Stem and crown divergence estimates (6.36 Ma; 2.78 Ma) between A. floridensis and western sister taxa span a period of extensive dispersal by western biota along an arid Gulf Coast corridor. These phylogeographical and phylogenetic results yield a biogeographic profile consistent with the western origin hypothesis. Moreover, age estimates for the roach's peninsular residence complement those of several other endemics, favoring a Pliocene (or earlier) inception of the scrub ecosystem. We argue that eastern versus western hypotheses are not mutually exclusive; rather, a composite history of colonization involving disparate biotas better explains the diverse endemism of Florida scrub. Abstract : Florida scrub is an unusual xeric ecosystem whose biotic sources have been alternatively ascribed to Pliocene dispersal from southwestern North America or Pleistocene migration within eastern North America. We provide a molecular biogeographic profile for a scrub endemic, the Florida sand cockroach ( Arenivaga floridensis ), that supports the western origin hypothesis. We argue that eastern versus western hypotheses are not mutually exclusive; rather, a composite history involving disparate biotas better explains the diverse endemism of Florida scrub.